Using Virtual Reality to Assess the Street Crossing Behavior of Pedestrians With Simulated Macular Degeneration at a Roundabout - Wu, Haojie; Ashmead, Daniel H.; Adams, Haley; Bodenheimer, Bobby (Frontiers in ICT, 2018)
This work investigates how pedestrian street crossing behavior at a virtual traffic roundabout is affected by central visual field loss. We exposed participants with normal vision to a first-person virtual experience of central visual field loss of variable size in the form of a simulated scotoma, an area of the visual field with degraded visual acuity. A larger size of scotoma influenced people to select longer gaps between traffic, and to wait longer before initiating a crossing. In addition, a gender difference was found for risk taking behavior. Male subjects tended to take more risk, as indicated by the selection of shorter gaps in traffic and a shorter delay before the initiation of a crossing. Our findings generally replicate those of studies done in real-world conditions using participants afflicted with genuine central vision loss, supporting the hypothesis that virtual reality is a safe and accessible alternative for investigating similar issues of public concern.